(untitled) (Economics and region, 2025)
Modern trends in global economic development demand new approaches to the efficient use of resources, which explains the growing interest in the concept of circular economy. This concept involves minimizing waste, optimizing material flows, and implementing environmentally-oriented business models that ensure the long-term sustainability of economic systems. In this context, port logistics plays a special role, as ports are key nodes in global supply chains and significant consumers of natural and material resources. However, traditional logistical models, which pose environmental risks, require a fundamental transformation. The lack of a systematic approach to managing the circular economy in ports significantly complicates the implementation of resource reuse practices, waste recycling, and the transition to alternative fuels, which hinders the sustainable development of the industry. This article explores conceptual approaches to managing the circular economy in port logistics and its role in the sustainable development of seaports. Since ports are key links in international logistics chains, their resource management and reduction of environmental impact are crucial for the further development of logistics. The main directions for forming circular supply centers in seaports are discussed, and a concept for managing the circular economy in seaports is developed based on the management of land, energy resources, and waste. The role of strategic planning and environmentally sustainable solutions for modernizing port infrastructure to meet the requirements of the circular economy is examined. The main directions for forming circular material flows in ports, particularly through waste recycling, reverse logistics, and innovative technologies, are identified. The development of conceptual foundations for managing the circular economy in port logistics will allow for the creation of effective mechanisms for implementing circular business models, which will contribute to the sustainable development of the domestic port industry in the face of global environmental challenges.